2011
DOI: 10.5897/ajpp11.062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc supplementation on hematological parameters of high performance athletes

Abstract: The purpose of the present study is to determine the effect of eight weeks zinc supplementation on the erythrocyte and leukocyte counts and other hematological parameters in male kick boxers. Twenty-four subjects were included in the study. They were equally divided into three groups as follows: Group EZ, training and receiving 2.5 mg/kg zinc supplement per day; Group SZ, receiving the zinc supplement but no training and Group E, who exercised but received no supplement. Erythrocyte, platelet and leukocyte cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 19 publications
1
7
1
1
Order By: Relevance
“…This result is consistent with the works of Silva et al (2006) and Polat (2011). This could be attributed to the beneficial effect of zinc as an antioxidant and immunostimulant.…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with the works of Silva et al (2006) and Polat (2011). This could be attributed to the beneficial effect of zinc as an antioxidant and immunostimulant.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Cordova et al [13] and Baltaci et al [27] also reported that using zinc supplement cannot affect the number of leukocytes after physical activities. In contrast to our results, Kilic et al [28] and Polat [29] found that physical activity can increase the number of leukocytes.…”
Section: Discussioncontrasting
confidence: 99%
“…[26] Baltaci et al reported increase of the number of erythrocytes in rats swimming in the pool while zinc deficiency led to the reduction of these erythrocytes. [27] On the other hand, Kilic et al [28] and Polat [29] demonstrated that zinc supplementation and doing physical activities caused to a significant surge of the number of RBC, Hb, and HCT as compared to the others who only performed exercise and consumed no zinc supplement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suplementasi zink 22 mg/hari terhadap atlet sepakbola laki-laki pada studi sebelumnya (12) memberikan hasil adanya peningkatan kadar plasma zink dan Fe eritrosit, penurunan kadar zink urin, serta penurunan fragilitas eritrosit, dan tidak memberikan efek samping penurunan kadar plasma Fe dan Cu. Selain itu, suplementasi zink sebanyak 2,5 mg/kgBB/hari pada atlet tinju laki-laki menghasilkan adanya perbaikan jumlah eritrosit, leukosit, hemoglobin, dan hematokrit dibandingkan dengan kelompok tanpa suplementasi (13).…”
Section: Pendahuluanunclassified